Transforming emergency care for older adults - Hwang, Ula (2013)
Already crowded and stressful, US emergency departments are facing the challenge of serving an aging population that requires complex and lengthy evaluations. Creative solutions are necessary to improve the value and ensure the quality of emergency care delivered to older adults while more fully addressing their complex underlying physical, social, cognitive, and situational needs. Developing models of geriatric emergency care, including some that are already in use at dedicated geriatric emergency departments, incorporate a variety of physical, procedural, and staffing changes. Among the options for “geriatricizing” emergency care are approaches that may eliminate the need for an emergency department visit, such as telemedicine; for initial hospitalization, such as patient observation units; and for rehospitalization, such as comprehensive discharge planning. By transforming its current safety-net role to becoming a partner in care coordination, emergency departments have the opportunity to better integrate into the broader health care system, improve patient health outcomes, contribute to optimizing the health care system, and reduce overall costs of care—keys to improving emergency care for patients of all ages.